2001
DOI: 10.1080/107175401317245903
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Human Intact Erythrocytes Loaded by Enalaprilat

Abstract: In vitro characteristics of the human erythrocytes loaded by enalaprilat have been evaluated. Erythrocytes obtained from a healthy volunteer were loaded by enalaprilat using the hypotonic preswelling method, and the loading parameters, drug-release kinetics, hematological indices, particle size distribution, scanning electron microscopy view, osmotic and turbulence fragilities, and deformability of the resulting carrier cells were determined along with the sham encapsulated and unloaded cells. Carrier erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 7 publications
9
44
0
1
Order By: Relevance
“…The overall loss of hemoglobin from the erythrocytes upon loading procedure was expected because the procedure is destructive in nature. In similar studies (Kravtzoff et al, 1990;Garin et al, 1996;Hamidi et al, 2001), all of these parameters were found to be lower in carrier erythrocytes than in normal unloaded cells. This finding is consistent with the results of Hamidi et al (2001).…”
Section: Resultsmentioning
confidence: 60%
“…The overall loss of hemoglobin from the erythrocytes upon loading procedure was expected because the procedure is destructive in nature. In similar studies (Kravtzoff et al, 1990;Garin et al, 1996;Hamidi et al, 2001), all of these parameters were found to be lower in carrier erythrocytes than in normal unloaded cells. This finding is consistent with the results of Hamidi et al (2001).…”
Section: Resultsmentioning
confidence: 60%
“…In contrast, the results of other studies have shown that turbulence fragility of the carrier erythrocytes increases significantly in comparison with the normal unloaded cells. 1,3,4,7 From the data in Table 4, no significant changes are evident in three hematological indices of nanoparticles-loaded erythrocytes, as expected from the gentle nature of the loading method used. However, these differences are higher in the case of shamencapsulated and drug-loaded cells.…”
Section: In Vitro Characterization Of Carrier Erythrocytesmentioning
confidence: 95%
“…1 Although erythrocytes are the most abundant and readily available cells of the human body, they have gained the highest and the most extensive attention among other cellular carriers for time-controlled or targeted delivery of the drugs and other bioactive agents. [1][2][3][4][5][6][7] In fact, the term "carrier erythrocyte" was first introduced in 1979 to describe the drug-loading capacity of the erythrocytes. 1 There are a series of advantages encouraging the wide spread application of erythrocytes in drug delivery, including, mainly, biocompatibility, complete biodegradability, long life span in circulation, possibility of targeted drug delivery to the reticuloendothelial system (RES) organs, relatively simple and inert intracellular environment, ease of handling, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit the mechanical strength of the membranes, packed RBC (0.5 ml) were suspended in TBS (10 ml) and shaked vigorously using an orbital shaker at 2000 rpm for 4 h. A portion (0.5 ml) of suspension was withdrawn during 0-4 h, centrifuged and the absorbance of the supernatant was determined spectrophotometrically at 540 nm. The hemoglobin release (%) was determined in reference to a completely lysed cell suspension [38]. The number of complement-regulatory proteins/cell was also determined [39] in which the median values from histograms plot were converted to arbitrary units in a linear scale (1-1024 channels).…”
Section: Surface Plasmon Resonance (Spr)mentioning
confidence: 99%